‘A star in the sky’: traditional nursery rhymes as a pedagogical tool for Teochew language classes in Singapore - Ng, Nicole Zhi Ee (Nanyang Technological University, 2023)
The status of the Teochew language in Singapore is declining. While efforts to revitalize the language have emerged, little research has been done on how to improve this urgent process, particularly for Teochew language classes. Research in foreign language teaching and other language revitalization efforts suggest the potential of nursery rhymes as an effective pedagogical tool in language classes. Thus, this study examines the potential efficacy of traditional Teochew nursery rhymes in local Teochew classes for adults in terms of improving classroom engagement and the understanding and retention of prosody, pronunciation, grammar, and vocabulary. Twenty-eight participants, divided into two groups, received a lesson on basic Teochew. One group was taught basic Teochew without nursery rhymes and one group was introduced to a traditional nursery rhyme related to the content of the class. The participants were tested at three time points including a class evaluation survey immediately after the lesson. The findings showed that nursery rhymes did not impact engagement and learning in these classes. The lack of differences in the two groups was attributed to the sampling which may have attracted participants who are more motivated to learn Chinese vernaculars. The study, however, provides insights on the needs of aspiring Teochew speakers and how pedagogical tools may be incorporated more effectively into local revitalization efforts. As alternatives, classroom storytelling and Master/Apprentice programmes with elder speakers may be considered in future Teochew revitalization strategies, as they can enable long-term language immersion and contextualization outside the classroom. Subsequent studies may reveal different results if nursery rhymes are incorporated into a more rigorous series of Teochew classes and quizzes.